Improving the literacy quality of public communication Covid-19 pandemic madrasah-based educational institutions through digital skills - Tantan Hermansah (Faculty of Dakwah and Communication, Walisongo State Islamic University, 2022)
Purpose – This article aims to describe the quality of communication literacy of the Covid-19 pandemic in madrasah-based educational institutions in the City and Regency of Bogor.Method - This study uses qualitative research with a descriptive analysis approach through direct field observations and Focus Group Discussions (FGD). The subjects in the study were six (6) Covid 19 Madrasah Task Forces in the City and District of Bogor.Result - The results of this service activity show that it is necessary to increase the capacity of each Madrasa Covid-19 Task Force through training and assistance and increasing understanding and communication skills so that the public gets a clear, firm, and definite understanding.Implication – the Task Force was then assisted because it was in the context of community development, so the desired process was by the planning. Lastly is monitoring and evaluation so community empowerment activities can be improved if there are still deficiencies.Originality - This research is based on improving the communication literacy quality of the Covid-19 pandemic 19 madrasa-based educational institutions through visual products to be strategic and important.***Tujuan – Tujuan dari pemberdayaan masyarakat ini adalah untuk menjelaskan gambaran kualitas literasi komunikasi pandemi Covid-19 di lembaga pendidikan berbasis madrasah di Kota dan Kabupaten Bogor.Metode – Metode dalam penelitian ini menggunakan jenis penelitian kualitatif dengan pendekatan analisis deskriptif melalui observasi lapangan secara langsung dan Focus Group Discussion (FGD). Subyek dalam penelitian ini adalah enam (6) Satgas Covid 19 Madrasah di Kota dan Kabupaten Bogor.Hasil - Hasil kegiatan pengabdian ini menunjukkan perlunya peningkatan kapasitas masing-masing Satgas Covid-19 Madrasah melalui pelatihan dan pendampingan serta peningkatan pemahaman dan keterampilan komunikasi agar masyarakat mendapatkan pemahaman yang jelas, tegas dan pasti.Implikasi – Satgas kemudian diberikan pendampingan, karena dalam rangka pengembangan masyarakat sehingga proses yang diinginkan sesuai dengan perencanaan. Terakhir adalah monitoring dan evaluasi agar kegiatan pemberdayaan masyarakat dapat ditingkatkan jika masih terdapat kekurangan.Orisinalitas - Penelitian ini dilatarbelakangi oleh peningkatan kualitas literasi komunikasi lembaga pendidikan berbasis madrasah 19 pandemi Covid-19 melalui produk visual menjadi strategis dan penting.